The influence of the modulus–density relationship and the material mapping method on the simulated mechanical response of the proximal femur in side-ways fall loading configuration. Issue 7 (July 2016) - Helgason, B.; Gilchrist, S.; Ariza, O.; Vogt, P.; Enns-Bray, W.; Widmer, R.P.; Fitze, T.; Pálsson, H.; Pauchard, Y.; Guy, P.; Ferguson, S.J.; Cripton, P.A.
Highlights: We model 16 human femurs tested in a side-ways fall loading configuration. We use 10 modulus density relationships and 5 material mapping methods. Validation outcome is highly sensitive to both input variables. Abstract: Contributing to slow advance of finite element (FE) simulations for hip fracture risk prediction, into clinical practice, could be a lack of consensus in the biomechanics community on how to map properties to the models. Thus, the aim of the present study was first, to systematically quantify the influence of the modulus–density relationship ( E – ρ ) and the material mapping method (MMM) on the predicted mechanical response of the proximal femur in a side-ways fall (SWF) loading configuration and second, to perform a model-to-model comparison of the predicted mechanical response within the femoral neck for all the specimens tested in the present study, using three different modelling techniques that have yielded good validation outcome in terms of surface strain prediction and whole bone response according to the literature. We found the outcome to be highly dependent on both the E – ρ relationship and the MMM. In addition, we found that the three modelling techniques that have resulted in good validation outcome in the literature yielded different principal strain prediction both on the surface as well as internally in the femoral neck region of the specimens modelled in the present study. We conclude that there exists a need to carry out a more comprehensive validation study for the SWF loading mode to identify which combination of MMMs and E – ρ relationship leads to the best match for whole bone and local mechanical response. The MMMs tested in the present study have been made publicly available athttps://simtk.org/home/mitk-gem .